Membangun Identitas Brand Melalui Strategi Branding Dan Digital Marketing Bagi Pemasaran Produk UMKM Desa Karangan - Devina Zulia Rahmatin; Dea Naurotul Jannah; Dwi Nur Hidayati; Winnarti Ningsih; Tasya Febriyanti; Putri Laili Susanti; Mu’tasim Billah (Universitas Muhammadiyah Manado, 2023)
The problems faced by MSMEs are usually caused by the lack of breadth of product marketing reach. MSMEs in Karangan Village, Bareng District, also have problems in terms of product marketing. It is based on less attractive marketing. MSME players also lack creativity in marketing development. The purpose of this activity is to increase the knowledge of MSME actors about the importance of digital media for marketing and also build product identity. The methods used in this community service activity are survey and observation, interview, discussion, and application. The results obtained from this community service activity are marketing assistance activities by utilizing digital media and assistance in making attractive logo and product packaging designs, providing knowledge to MSME actors about digital media that can be used in product marketing, and can improve brand identity.